PENGARUH INFLASI, NILAI TUKAR, SUKU BUNGA DAN INDEKS NIKKEI 225 TERHADAP INDEKS HARGA SAHAM GABUNGAN DI ASEAN - Yulidia Rohmawati; Idah Zuhroh (Jurnal Ilmu Ekonomi JIE, 2019)
The purpose of this study was to analyze the effect inflation, exchange rates, interest rates and the Nikkei 225 Index on the Composite Stock Price Index in five ASEAN countries, namely Indonesia, Malaysia, Singapore, the Philippines and Thailand. Using panel data regression analysis using Eviews 9 since 2002 until 2016. The results of this study show that inflation and exchange rates partially have a significant negative effect on the stock price index in ASEAN, the Nikkei 225 index has a significant positive effect while the interest rate has no significant effect on Composite Stock Price Index. Simultaneously all variables influence the JCI and obtained an adjusted R-square of 67,92%, which means that 67,92% of the Composite Stock Price Index in ASEAN is explained by the four variables.